Perancangan Aplikasi Untuk Pemegang Kunci Ganda - Nonot Wisnu Karyanto; Wing Wahyu Winamo; Roy Rudolf Huizen (Melek IT : Information Technology Journal, 2016)
Data security is very important with the increasingly rapid development of technologies as well as the possibility of handling the security of data processing which will be managed by two or more people then need a plan for securing data in a PC in order to be secure and that data is maintained integrity, keauthentikannya of the parties unauthorized or intentionally damage data. In this study design how the login process with two di fferent passwords and password holders of the first two are not mutually know, besides testing the single login password to login two passwords.